Investigating The Influence of Teacher Aggression on Student Academic Motivation in Province of Sindh, Pakistan - Ahmed, Maroof; Soomro, Aizaz Ali; Haleema, Haleema (Universitas Teuku Umar, 2023)
The present study aimed to explore the impact of teacher aggressive behaviors on student academic motivation in Sindh, one of the provinces in Pakistan. A descriptive survey research design was employed, utilizing a sample of 120 public school teachers (70 female and 50 male). Data was collected using a researcher-developed instrument called the